Effect of folpet on hypoglycaemia, intestinal microbiota, and drug resistance genes in mice - Cao, Tingting; Guo, Yajie; Lin, Liangqiang; Wang, Dan; Liu, Zhiyang; Zou, Xuan; Ke, Yuebin; Lv, Ziquan (BMC microbiology, 2025)
Folpet is a nonspecific sulfonamide fungicide widely used to protect crops from mildew. However, the in vivo effects of folpet on glucose metabolism homeostasis, gut microbiota, and abundance of drug resistance genes remain unknown. The purpose of this study was to assess the effects of the pesticide, folpet, on glucose metabolism homeostasis, and folpet-induced changes in the intestinal microbiota and resistance genes in mice. Mice were orally administered folpet at 0, 1, 10, and 100 mg/kg body weight/day for 5 weeks. Blood sugar levels in mice were measured after 5 weeks of folpet administration. Metagenomic sequencing and drug resistance gene analyses were performed to explore changes in the abundance of gut microbiota members and drug resistance genes in mice after folpet administration. Correlation analysis was performed using metabolomics to explore the relationship between intestinal microbiota, drug resistance genes, and glucose metabolism. Mice in the folpet group had significantly lower blood glucose levels than those in the control group. The abundance of Atopobium, Libanicoccus, Collinsella, and Parabacteroides in the intestinal microbiota of folpet-treated mice was significantly higher than that in the control group. However, the abundance of Mailhella, Bilophila, Roseburia, and Bacteroides were reduced in folpet-treated mice. Compared with the control group, the abundance of APH6-Ic and AAC6-Ie-APH2-Ia resistance genes in mice treated with folpet significantly increased. The abundance of tetQ, ermE, and BahA resistance genes was significantly reduced after folpet treatment. Folpet is associated with changes in the abundance of gut microbiota in mice and may also affect the abundance of drug-resistance genes and the regulation of blood glucose levels.